Physical-layer counterattack strategies for the internet of bio-nano things with molecular communication - Huang, Yu; Wen, Miaowen; Lin, Lin; Li, Bin; Wei, Zhuangkun; Tang, Dong; Li, Jun; Duan, Wei; Guo, Weisi (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Molecular communication (MC) is an emerging new communication paradigm where information is conveyed by chemical signals. It has been recognized as one of the most promising physical layer techniques for the future Internet of Bio-Nano Things (IoBNT), which enables revolutionary applications beyond our imagination. Compared with conventional communication systems, MC typically demands a higher security level as the IoBNT is deeply associated with the biochemical process. Against this background, this article first discusses the security and privacy issues of IoBNT with MC. Then, the physical-layer countermeasures against the threat are presented from an interdisciplinary perspective concerning data science, signal processing techniques, and the biochemical properties of MC. Correspondingly, both the keyless and key-based schemes are conceived and revisited. Finally, some open research issues and future research directions for secrecy enhancement in IoBNT with MC are put forward.